Three-Dimensional Printing for Oral Pharmaceutical Dosage Forms - Kim, Ji Hoon; Kim, Kyeongjin; Jin, Hyo Eon (Journal of Pharmaceutical Investigation, 2022)
Background: The advent of three-dimensional (3D) printers in the pharmaceutical industry is making a leap forward. 3D printing technology can be applied to patient-friendly drug development by adjusting drug dose, shape, flavor, and dug release pattern to meet individual patient needs. Oral pharmaceutical dosage forms can be printed using various 3D printing technologies, and it is necessary to understand the characteristics and applied conditions of each printing technology. Area covered: This article covers five commonly used 3D printing technologies (binder jetting, material extrusion, vat photopolymerization, material jetting, and powder bed fusion) and the properties of four oral pharmaceutical dosage forms (immediate-release tablets, modified-release tablets, orodispersible tablets, and orodispersible films) produced using 3D printing technology. Expert opinion: 3D printing technologies are suitable for preparing drugs in oral dosage forms. Based on the understanding of the factors of 3D printing that influence drug release, it is possible to develop patient-friendly 3D-printed drugs for various active pharmaceutical ingredients (APIs).
Keywords: Immediate-release tablet; Modified-release tablet; Oral dosage form; Orodispersible film; Orodispersible tablet; Three-dimensional printing technology